Gerard Manley Hopkins's poetic art as "current language heightened" : (with reference to selected sonnets and in the light of contemporary stylistic theory) - McDermott, Lydia Eva (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 1985)
The aim of this thesis is twofold: To examine Hopkins's writings on poetics and to relate these to modern theories of poetic stylistics; and to show, through an examination of two sets of Hopkins sonnets, the ways in which Hopkins's writings on language and poetics are reflected in his verse (Introductory outline, p. 5)
Keywords: Hopkins, Gerard Manley, 1844-1889; English poetry -- 19th century -- History and criticism